A model for the reaction kinetics of main and side reactions during the industrial production of trioxane, and its applications. Issue 8 (13th March 2018) - Zhang, Xianming; Hu, Yufeng; Ma, Weiting
Abstract: BACKGROUND: Trioxane is industrially synthesized by cyclotrimerization of formaldehyde in [formaldehyde–H2 SO4 (catalyst)–H2 O]. A rapid expansion of trioxane production facilities has occurred worldwide, which requires a reliable model for the reaction kinetics of main and side reactions, and a deep understanding of underlying mechanisms of conversion and selectivity. RESULTS: Such a model is developed on the basis of our newly established reaction pathways for product and by‐products, and component activities calculated by the extended UNIFAC models. Reaction kinetics data are measured and utilized to determine model parameters. The new model offers correct descriptions of the reaction kinetics of main and side reactions that occur under industrial working conditions. The model calculation results are used to illustrate the mechanisms that govern conversion and selectivity, and illustrate the roles of catalysts and salt additives in industrial production of trioxane through the reactive distillation process. CONCLUSIONS: The principal prediction results are that both conversion and selectivity can be significantly enhanced by developing new catalysts and salt additives to decrease the rate constant for decomposition reaction of trioxane to formaldehyde, and new catalytic mixtures should integrate catalysis with extractive distillation. All of the model predictions are consistent with experimental results. © 2018 Society of Chemical Industry